(untitled) (Jurnal Proaksi, 2022)
The ethical dilemma that an auditor faces when carrying out an ethical decision-making process that includes decisions between limiting quality. IAI gives sanctions to KAPs that violate auditing standards, so there is a crisis of confidence for auditor careers in Indonesia. This study aims to obtain empirical evidence of the influence of audit experience, professional commitment, ethical orientation and time budget pressure on external auditors’ ethical decision making. Surabaya Public Accounting Firm is an object of observation. Auditors at 47 KAP Surabaya in 2020 are the population of this study. The research sample consisted of 82 external auditors. This research method uses Simple Random Sampling. Generalized Structured Component Analysis (GeSCA) is the technique of this research. The output results of this study explain that audit experience, professional commitment, ethical orientation and time budget pressure influence external auditors’ ethical decision making. Keywords: Audit, Commitment, Ethics, Budget, Ethics.